PENERAPAN KODE ETIK SEBAGAI UPAYA MENCEGAH TINDAKAN KEKERASAN YANG DILAKUKAN ANGGOTA DPRD DALAM MELAKSANAKAN TUGAS - Fahmiron, Fahmiron; Syafrinaldi, Syafrinaldi (UNES Law Review, 2023)
Article 3 paragraphs (1) and (4) of Padang Pariaman Regency DPRD Regulation Number 2 of 2020 concerning the DPRD Code of Ethics. One violation of the code of ethics is violence in carrying out duties. This research is legal research with descriptive-analytical specifications. From the results of the internal meeting, the members of the DPRD who were in conflict were summoned. The Honorary Board verbally reprimanded DPRD members with the initials H and J. Then they were given directions and input on what they had done in DPRD meeting activities. The two DPRD members were asked not to repeat their actions and attitudes and to respect the DPRD district regulations and procedures. Padang Pariaman. Obstacles in the Implementation of the Code of Ethics as an Effort to Overcome Violent Behavior by DPRD Members in Carrying Out Their Duties at the Padang Pariaman Regency DPRD are in the form of External Obstacles, namely statutory regulations. Weaknesses in research techniques in Article 51 letter b of Government Regulation Number 53 of 2005 concerning Amendments to Government Regulation Number 25 of 2004 concerning Guidelines for Drafting the Standing Orders of the Regional People's Representative Council which states that document inspection is only sufficient for formal evidence in the form of written allegations and the identity of the reporter and through requests for information and explanations from witnesses and/or those concerned as well as an examination of documents or other evidence.